Competitive Job Seekers: When Sharing Less Leaves Firms at a Loss - Gaurav Chiplunkar; Erin Kelley; Gregory Lane (Institute of Labor Economics (IZA), 2024)
We study how job-seekers share information about jobs within their social network, and its implications for firms. We randomly increase the amount of competition for a job and find that job-seekers are less likely to share information about the job with their high ability peers. This lowers the quality of applicants, hires, and performance on the job - suggesting that firms who disseminate job information through social networks may see lower quality applicants than expected for their most competitive positions. While randomly offering higher wages attracts better talent, it is not able to fully overcome these strategic disincentives in information sharing.
Keywords: L14; M51; O12; 330; job information; social networks; labor markets